2017
DOI: 10.1111/tpj.13555
|View full text |Cite
|
Sign up to set email alerts
|

C‐Glycosyltransferases catalyzing the formation of di‐C‐glucosyl flavonoids in citrus plants

Abstract: Citrus plants accumulate many kinds of flavonoids, including di-C-glucosyl flavonoids, which have attracted considerable attention due to their health benefits. However, the biosynthesis of di-C-glucosyl flavonoids has not been elucidated at the molecular level. Here, we identified the C-glycosyltransferases (CGTs) FcCGT (UGT708G1) and CuCGT (UGT708G2) as the primary enzymes involved in the biosynthesis of di-C-glucosyl flavonoids in the citrus plants kumquat (Fortunella crassifolia) and satsuma mandarin (Citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 39 publications
3
86
0
1
Order By: Relevance
“…Unlike O-glycosylation that terminates flavone biosynthesis, Cglycosylation occurs on unstable intermediates prior to the final scaffold formation. Except for PiUGT43 25 , GtUF6CGT1 26 , and TcCGT1 27 , all characterized CGTs to date belong to the UGT708 family [15][16][17][18]22,23 , indicating that the UGT708 family may be specialized for C-glycosylation of phenylpropanoids and flavonoids. Through this study, we have significantly expanded the knowledge on monocot UGT708A family by not only tripling the number of known CGTs from current 12 (2 monocot, 7 dicot UGT708, and 3 non-UGT708 CGTs) to 38, but also by revealing a group of hitherto unknown group that could recognize UDP-Ara (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike O-glycosylation that terminates flavone biosynthesis, Cglycosylation occurs on unstable intermediates prior to the final scaffold formation. Except for PiUGT43 25 , GtUF6CGT1 26 , and TcCGT1 27 , all characterized CGTs to date belong to the UGT708 family [15][16][17][18]22,23 , indicating that the UGT708 family may be specialized for C-glycosylation of phenylpropanoids and flavonoids. Through this study, we have significantly expanded the knowledge on monocot UGT708A family by not only tripling the number of known CGTs from current 12 (2 monocot, 7 dicot UGT708, and 3 non-UGT708 CGTs) to 38, but also by revealing a group of hitherto unknown group that could recognize UDP-Ara (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The in planta CGF biosynthesis ( Fig. 1) has been so far partially established in a few monocotyledons and dicotyledonous plants [15][16][17][18][19][20][21][22][23] . The pathway is understood to involve upstream precursor biosynthesis and several downstream modification enzymes including cytochrome P450s and glycosyltransferases.…”
mentioning
confidence: 99%
“…Recently, the enzymatic synthesis of flavonoid C ‐glycosides by plant CGTs has attracted considerable interest (Supporting Information, Scheme S1) . The 2‐hydroxyflavanone CGTs, including OsCGT from Oryza sativa , FeCGTa and FeCGTb from Fagopyrum esculentum , UGT708D1 from Glycine max , FcCGT from Fortunella crassifolia , and CuCGT from Citrus unshiu , utilize the open‐circular form of 2‐hydroxyflavanones as substrates to produce flavone C ‐glycosides after dehydration. The bifunctional glycosyltransferase (GT) UGT708A6 from Zea mays uses the closed‐circular form of 2‐hydroxyflavanones as substrates .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, citrus UGTs genes are involved in metabolism [34] and expressed during growth and development [35]. The citrus UGTs are involved in flavonoids biosynthesis [35,36] and stimulates the anthocyanin biosynthesis in citrus [37]. Based on our (Additional file 2) and published transcriptome data [38], we have selected UGTs genes and confirmed that the UGT78D3 gene was differentially expressed in citrus specie (Citrus sinensis) by quantitative real time PCR (qRT-PCR) (Additional file 1).…”
Section: Selection and Overexpression Ugts Genementioning
confidence: 74%